Technical Assistance in Physical Education, Sports, and Health Learning at SMK Nusantara Tanjung Jabung Timur - Kresno Bayu Edi Putra; Zaenal Abidin; Kurniawan; Huong Le; Hidayat (CV. Zabags Qu Publish, 2025)
This study analyzes the implementation of technical assistance in the teaching of Physical Education, Sports, and Health (PJOK) integrated with sharia-based economic values at SMK Nusantara Tanjung Jabung Timur. Rooted in the need to strengthen students’ sense of responsibility, honesty, cooperation, accountability, and health awareness within a vocational education setting, this research adopts a qualitative case study approach using observations, interviews, and documentation. The findings indicate that embedding sharia values into sports activities fosters positive behavioral development through hands-on experience, rotating team roles, and structured value-oriented reflection. Three major themes emerge: the internalization of honesty and amanah (trustworthiness), the enhancement of teamwork and responsibility, and the development of health awareness as an expression of viewing the body as an entrusted responsibility. This study provides a practical contribution by offering a replicable model of technical assistance for PJOK teachers and a theoretical contribution by expanding Islamic character education through the integration of sharia economic principles within vocational school contexts. The results also highlight opportunities for future research using broader samples and quantitative or mixed-method designs to further examine the model’s effectiveness.